Shift Work System Analysis of Store Employee Fatigue Using the Subjective Self Rating Test and Independent Sample T Test Methods (Case of Sports Station Plaza Surabaya) - Baihaqi, Ahmad Reza; Suryadi, Akmal (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
This study analyzed the initial symptoms of fatigue and measured the level of fatigue with the subjective self rating test method as the subjective method, the CVL (Cardiovascular Load) method as the objective, and the independent sample t test at the Plaza Surabaya sports station. shop. Shift work in the workshop has the potential to pose health risks in the form of fatigue due to differences in physical workload experienced in each shift. Sports Station Plaza Surabaya outlets face work activity problems that are at risk of ergonomics, with several worker complaints due to work shifts that only do rotating shifts per month and unclear employee jobdesk placements. The Subjective Self Rating Test method is used to identify early symptoms of employee fatigue by filling out a questionnaire, the CVL method is used to measure pulse to obtain the level of physical workload fatigue experienced by employees. While the independent sample t test test is to find out whether there is a significant difference in the level of shift fatigue at the Sports Station Plaza Surabaya store. get the highest classification value in shift 1, for the independent t test test method get a significance value of 0.01 which means there is a significant difference in the level of worker fatigue in shift 1 and shift 2.